GENERASI MUDA YANG BERKARAKTER DAN BERMORAL: WHY NOT? - Riski Erisah Simanjuntak; Risma Darma Ulima Banurea; Rospita Pasaribu; Silvia Ningsih Berutu; Third Princes Siregar; Damayanti Nababan (Ta'rim: Jurnal Pendidikan dan Anak Usia Dini, 2022)
This journal discusses the moral education of today's children from a Christian perspective. The term today's children in Indonesia is better known as Kids Age Now. Kids Age Now is actually an allusion to the unnatural behavior of today's children. Education that is distanced and moral is a series of basic moral principles and the virtues of attitudes and character that children must have and make habits from a beginner's time until they become obedient to God. This research is a library research with a literature study approach through reference sources, such as books, articles, journals, and other scientific sources used in the discussion of this research. To deal with the problems of Kids Age Now, morals that are sourced from the Bible and Christian youth activities are needed. The goal is that today's children become children who have good character and are commendable. Being a Christian youth with character and morals is not easy, because Christian youths with character and morals are youths whose behavior follows the teachings of Christ, have Bible-based morals, are able to be good Christian youths, and do the right things and what Christ wants.